2018
DOI: 10.1155/2018/7406027
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hyperbaric Oxygenation, Contrary to Intermittent Hyperbaric Oxygenation, Adversely Affects Vasorelaxation in Healthy Sprague‐Dawley Rats due to Increased Oxidative Stress

Abstract: The present study was aimed at assessing endothelium-dependent vasorelaxation, at measuring superoxide production in the aorta and femoral artery, and at determining antioxidative enzyme expression and activity in aortas of male Sprague-Dawley rats (N = 135), randomized to an A-HBO2 group exposed to a single hyperbaric oxygenation session (120′ of 100% O2 at 2.0 bars), a 24H-HBO2 group (single session, examined 24 h after exposure), a 4D-HBO2 group (4 consecutive days of single sessions), and a CTRL group (unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 62 publications
4
31
0
Order By: Relevance
“…The observed decrease in mean arterial pressure is consistent with our previous studies, which discuss this issue [ 18 , 29 ]. Oxidative stress induced impaired baseline AChIR and HIR in the A-HBO 2 group, which was also previously described and discussed in our previous study [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The observed decrease in mean arterial pressure is consistent with our previous studies, which discuss this issue [ 18 , 29 ]. Oxidative stress induced impaired baseline AChIR and HIR in the A-HBO 2 group, which was also previously described and discussed in our previous study [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, independently of hypoxic or normoxic conditions, free radicals are needed to express HIF-α [ 36 , 37 ]. In acute HBO 2 exposure, the oxidative stress is increased [ 18 ]. Previously, it has been shown that HIF-1 and -2 levels are increased in HBO 2 treatment due to increased ROS production [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In traumatic brain injury, HBO attenuates inflammatory responses by limiting production of inflammatory mediators, creating better environment for repair and regeneration [12]. However, these effects are dependent on treatment parameters-pressure and duration on the treatment [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This trend was more evident between patients with a history of hypertension compared to normotensive patients ( Figure 2 ); it is likely that the vasoconstrictive response becomes more pronounced after treatment, and it may either represent an improved arteriolar smooth muscle activity or a lack of vasorelaxation. While it has been described that repetitive HBOT improves the vasorelaxation [ 22 , 23 , 24 ], increased vascular stiffness might play a role in impairing this response in patients with a history of hypertension.…”
Section: Discussionmentioning
confidence: 99%